Recent Advances in Glycosidase Probes Used in Escherichia Coli Detection - Wei, Xianhu; Feng, Ying; Chen, Minling; Zhang, Shuhong; Chen, Moutong; Zhang, Jumei; Zhang, Youxiong; Ye, Qinghua; Ding, Yu; Xue, Liang; Wu, Qingping (Current Medicinal Chemistry, 2021)
Pathogenic Escherichia coli poses a serious threat to global public health and is especially dangerous with the increase of antibiotic resistance. β-Glucuronidase (GUS) and some other glycosidases can serve as useful biomarkers or indicators for the detection of E. coli. The probes made up of a glycosyl residue (recognition group), a label or reporter group, and a linkage that is generally a direct glycosidic bond, are powerful analytical tools. Upon hydrolysis of the glycosidic linkages by the corresponding glycosidases, these probes irreversibly release detectable labels or reporter molecules. A variety of such glycosidase probes have been developed and applied for the detection of E. coli or the development of various corresponding detection methods. This paper provides an overview of recent advances in this field, covering the development and applications of chromogenic, fluorogenic, luminogenic, and electrochemical glycosidase substrates. The challenges and opportunities in the probe development for detection of E. coli are also discussed.
Keywords: Bacterial pathogens